Five-year treatment outcomes with four types of implants in the posterior maxilla and mandible in partially edentulous patients: A retrospective study - (:unkn) unknown (My University, 2011)
Purpose: The aim of this retrospective study was to evaluate the outcomes, after 5 years of functional loading, of four different types of implants supporting prostheses in the posterior maxilla and mandible. Materials and Methods: Patients missing posterior teeth were treated with implants between 1998 and 2004. The implants were evaluated by clinical and radiographic parameters and Plaque Index, Sulcus Bleeding Index (BI), peri-implant probing depths (PD), and marginal bone loss (MBL) were recorded. Repeated-measures analysis of variance, Kruskal-Wallis, and Wilcoxon signed rank tests were used for statistical analysis. Results: In all, 244 implants were placed in 83 patients: 86 Straumann implants, 35 Swiss Plus implants, 90 Camlog implants, and 33 Frialit implants. Patients received 93 single crowns and 71 fixed partial dentures (FPDs). Nine FPDs were cemented to both implants and natural teeth, and 62 FPDs were supported by implants only. At the 5-year recall, plaque accumulation was significantly higher than at baseline for all groups (P = .01). Mean PD was 1.8 mm in the maxilla and 1.6 mm in the mandible. The mean PD values were 1.77 ± 0.52 mm for Straumann, 1.87 ± 0.64 mm for Swiss Plus, 2.33 ± 0.58 mm for Camlog, and 2.29 ± 0.46 mm for Frialit. MBL was 0.19 ± 0.07 mm for Straumann, 0.27 ± 0.06 mm for Camlog, 0.26 ± 0.07 mm for Swiss Plus, and 0.24 ± 0.07 mm for Frialit. The mean MBL of Straumann implants was significantly lower than that seen in the other groups (P = .001). Conclusion: The four types of implants resulted in similar clinical success after 5 years. © 2011 by Quintessence Publishing Co Inc.
Keywords: Osseointegration; Partial edentulism; Posterior mandible; Posterior maxilla; Titanium implants